Accreditation and the Construction Industry : Five Approaches to Countervailing Employer Power - Rose, Joseph (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1973)
In this paper, the author aims at describing the various legislative approaches to accreditation which have been adopted and at evaluating the strengths and weaknesses of different efforts to reduce employer fragmentation and redress the imbalance of power within the industry